2019
DOI: 10.3233/jad-181218
|View full text |Cite
|
Sign up to set email alerts
|

Acute Anti-Inflammatory Markers ITIH4 and AHSG in Mice Brain of a Novel Alzheimer’s Disease Model

Abstract: Alzheimer's disease (AD) is the most common dementia and a progressive neurodegenerative disorder aggravated by chronic hypoperfusion (HP). Since a lot of evidence suggest that inflammations are related with AD pathology, we investigated the expression change of two anti-inflammatory markers, inter-alpha-trypsin inhibitor heavy chain H4 (ITIH4) and alpha-2-HS-glycoprotein (AHSG), in a novel AD model (APP23) with HP at 12 month of age. As compared with wild type (WT, n=10), immunohistochemical analysis showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…In fact, a recent report suggested an important role of pericyte for maintaining cerebral circulation and pleiotrophin secretion at NVU [44]. Our previous studies also reported that the mother proteins of these peptides (FAC and PPC1I) were upregulated and AHSG was downregulated in AD model mice, which were enhanced by chronic hypoperfusion [38,45]. These previous mice reports were confirmed in human AD brain samples in the present study ( Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, a recent report suggested an important role of pericyte for maintaining cerebral circulation and pleiotrophin secretion at NVU [44]. Our previous studies also reported that the mother proteins of these peptides (FAC and PPC1I) were upregulated and AHSG was downregulated in AD model mice, which were enhanced by chronic hypoperfusion [38,45]. These previous mice reports were confirmed in human AD brain samples in the present study ( Fig.…”
Section: Discussionsupporting
confidence: 90%
“…FBC and FAC are essential coagulation materials and key contributor of AD pathology [34,35]. PPC1I is a serpin superfamily, which regulates a pivotal coagulation/neuroinflammation in damaged brain [36,37], and anti-inflammatory AHSG is regulated under control of pro-inflammatory tumor necrosis factor-␣ [38,39]. Thus, the present data strongly suggest a new pathomechanism of AD, that is not simple A␤ and tau hypotheses but are in good accordance to our recent reports that suggested a neurovascular unit (NVU) damage and a neuroinflammation/plasticity of AD brain [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Inter-alpha-trypsin inhibitor was found deiminated in south polar skua plasma. It is an acute inflammatory marker [171] which functions as a protease inhibitor and is linked to a range of inflammatory responses [172], oxidative stress [173] and infection [174]. Furthermore, inter-α inhibitor proteins play roles in maintaining the resting state of neutrophils by regulating shape and reducing ROS production [175].…”
Section: Discussionmentioning
confidence: 99%
“…Although many of the mechanisms underlying the functional importance of IAIPs are not known, increases in IAIP expression are correlated with a diverse spectrum of pathological conditions including tissue injury and repair (Huth et al, 2015;Plaas et al, 2011;Tan, McGrouther, Day, Milner, & Bayat, 2011), and inflammation (Daveau et al, 1998;Garantziotis et al, 2007;Itoh et al, 1994;Kobayashi, 2006;Mizon, Mairie, Balduyck, Hachulla, & Mizon, 2001;Okroj et al, 2012;Seifert, Kurzinger, Hopt, & Wittel, 2013;Wakahara et al, 2005). Recent studies have also reported changes in the level of IAIPs after stroke (Kashyap et al, 2009) and Alzheimer's disease (Shi et al, 2019), suggesting that endogenous IAIPs may be integrally related to the pathogenesis of inflammatory-related brain disorders. In addition, systemic levels of IAIPs have been reported to be decreased in sepsis in neonates and adults (Chaaban et al, 2009;Degraeuwe & Nieman, 2010;Opal et al, 2007) and in necrotizing enterocolitis in neonates (Chaaban et al, 2010;Shah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%